Patient Satisfaction in Lumbar Decompression Surgery under Spinal Anesthesia: A Prospective Study - Rashada Farooqi, Aftab Ahmed, Fazal Wadood, Mewat Shah, Mashhood Alam Khan, Muhammad Mehboob Alam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Spine surgery, particularly in the lumbar region, is often associated with significant anxiety due to concerns about anesthesia, positioning, and postoperative discomfort. Traditionally performed under general anesthesia, lumbar decompression procedures are increasingly being done under spinal anesthesia to reduce complications and enhance recovery. This study aimed to evaluate patient satisfaction with spinal anesthesia for lumbar decompression surgery and to identify factors influencing their experience. Methods: This prospective study was conducted at Shamshad Aslam Hospital from July 2020 to June 2023. A total of 152 patients undergoing lumbar decompression under spinal anesthesia were enrolled. Patient demographics, intraoperative experiences, postoperative symptoms, and satisfaction levels were recorded using a structured questionnaire. Data were analyzed using SPSS version 27, with Pearson correlation applied to explore associations between patient variables and satisfaction (p < 0.05). Results: The majority of patients (91.5%) reported satisfaction with the overall surgical experience, and 94.1% indicated they would recommend spinal anesthesia for similar procedures. Despite comprehensive preoperative counseling, 30.9% experienced moderate to severe pain during needle insertion, 40.1% reported shivering, and 64.5% experienced nausea or vomiting. Chest discomfort in the prone position was noted in 82.9% of patients. Postoperative issues such as spinal headache, numbness, or urinary retention were reported by 11.9%, with most resolving within 48 hours. Older age, higher BMI, and longer surgical duration were negatively associated with satisfaction (p < 0.05). Conclusion: Spinal anesthesia for lumbar decompression surgery is a safe and well-accepted option, associated with high patient satisfaction and manageable complications. Careful patient selection and preoperative counseling can further improve outcomes. Keywords: Spinal anesthesia, lumbar decompression, patient satisfaction, prone positioning, postoperative symptoms, minimally invasive spine surgery.